The Autonomy of Repetition: Gilles Deleuze and the Autonomy of Migration - Herder, Janosik (Momentum Quarterly, 2016)
Recently, traditional theories about migration were challenged by the Autonomy of Migration approach. In this article I argue that the Autonomy of Migration approach puts forward an ambiguous reading of autonomy. This ambiguity ultimately results in two versions of the approach. The first version claims that migration is an absolutely autonomous force that is subject to control but independent from the political and economic context. The second puts forward a relational reading of autonomy and a rather vague interdependence of migration and its context. I assess this ambiguity by rereading Gilles Deleuze’s concepts of actuality and virtuality and present a somewhat difficult and counterintuitive concept of autonomy. Yet in order to understand the ambiguity found in the Autonomy of Migration approach and offer a perspective for further theorizing, Deleuze’s understanding of autonomy should be taken seriously. I conclude by showing that the autonomy of migration exists essentially in the form of repetition.